Pressure sensitive adhesives from natural rubber latex and oleic acid-based alkyds / Siti Fatimah Binti Mohd Mustafa - Mohd Mustafa, Siti Fatimah (2013)

(untitled)
Development of environmental friendly products have becomes increasingly important in the recent years. This project is environmental concerns and new developments in adhesive technology to create safe systems that reduce the emission of volatile organic compounds (VOCs). In this study, pressure sensitive adhesives (PSAs) were synthesized directly from latex by using alkyd derived from palm oil-based polyester as tackifier resin. Firstly, three different oil lengths 45, 47 and 65 of alkyd resins namely (Alk-45, Alk47 and Alk-65) were synthesized under fatty acid process by employing fusion cook technique. The prepared resins were later characterized by FTIR, NMR, TGA, GPC and DSC instruments. Then, the alkyds resins were converted into stable emulsion through emulsion inversion point method (EIP) with different surfactant mixture. Next, rheology test was carried out to characterize the properties of the emulsion. The test revealed that Alk-45 and Alk-47 emulsion with surfactant mixture S-8020 was the most stable emulsion, while surfactant mixture S-5050 produced the most stable emulsion for Alk-65. All alkyd emulsions showed non-Newtonian behaviour as revealed in rheological measurement. Alkyd emulsions were blended with NR latex in different ratios. The blends were stable for more than two weeks. PSA tapes were prepared by coating the blends onto a corona-treated polypropylene plastic backing. Subsequently, peel test, shear strength and adhesive weight per unit area of the PSA tapes were determined in accordance with the American Society for Testing and Materials (ASTM). From the study of adhesives properties, all NR/Alkyd blends exhibited good peel strength but low shear strength as compared to the commercial tapes. Among all, Alk-47 improved the peel strength of PSA tape better than the other two (Alk-45 and Alk-65) alkyd derived from palm oil based polyester resin.